Electronic anisotropies revealed by detwinned angle-resolved photo-emission spectroscopy measurements of FeSe. (20th October 2017) - Watson, Matthew D; Haghighirad, Amir A; Rhodes, Luke C; Hoesch, Moritz; Kim, Timur K
Abstract: We report high resolution angle-resolved photo-emission spectroscopy (ARPES) measurements of detwinned FeSe single crystals. The application of a mechanical strain is used to promote the volume fraction of one of the orthorhombic domains in the sample, which we estimate to be 80 % detwinned. While the full structure of the electron pockets consisting of two crossed ellipses may be observed in the tetragonal phase at temperatures above 90 K, we find that remarkably, only one peanut-shaped electron pocket oriented along the longer a axis contributes to the ARPES measurement at low temperatures in the nematic phase, with the expected pocket along b being not observed. Thus the low temperature Fermi surface of FeSe as experimentally determined by ARPES consists of one elliptical hole pocket and one orthogonally-oriented peanut-shaped electron pocket. Our measurements clarify the long-standing controversies over the interpretation of ARPES measurements of FeSe.